Strategic Sensitivity and Corporate Responsiveness of Fast Moving Consumer Goods Companies in Rivers State, Nigeria - Adim, Victor; Maclayton, Isoboye (Journal of Strategic Management, 2021)
Purpose: This study examined the relationship between strategic sensitivity and corporate responsiveness of fast moving consumer goods companies in Rivers State, Nigeria. Methodology: The study adopted a cross sectional survey research design. The population of this study was nine (9) fast moving consumer goods companies in Rivers State. Since the unit of analysis was at organizational level, only strategic managers were included. Five managers each were used for each company giving a total of 45 respondents. Census was adopted because the population was small. Primary data was collected using a 5-point Likert scaled questionnaire. The reliability of the instrument was achieved by the use of the Cronbach Alpha coefficient with all the items scoring above 0.70. The hypotheses were tested using the Spearman's Rank Order Correlation Coefficient with the aid of Statistical Package for Social Sciences version 23.0. The tests were carried out at a 95% confidence interval and a 0.05 level of significance. After data cleaning, only data for 38 respondents were used for data analysis. Findings: The findings revealed that there is a significant positive relationship between strategic sensitivity and corporate responsiveness of fast moving consumer goods companies in Rivers State, Nigeria. Specifically, strategic foresight and strategic insight were significantly and positively correlated with corporate responsiveness of fast moving consumer goods companies in Rivers State, Nigeria. Recommendation: The study recommends that fast moving consumer goods companies should build its capabilities of strategic foresight in examining the dynamic business environment and should constantly and proactively scan for opportunities and threats, in addition to strategies for lowering or reducing cost of production compare to other competitors.